2018
DOI: 10.1177/2473011418s00125
|View full text |Cite
|
Sign up to set email alerts
|

Custom 3D-printed Total Talar Prostheses Restore Normal Joint Anatomy Throughout the Hindfoot

Abstract: Category: Hindfoot Introduction/Purpose: Third generation total talar prostheses (TTP) are viable options for talar avascular necrosis (AVN) in the absence of neighboring joint pathology. The use of modern three-dimensional (3D) printing allows for the production of custom implants that exactly mimic the patient’s anatomy. The aim of this study is to determine the accuracy of 3D printing in reproducing a synthetic talus, and in doing so, restoring more normal anatomic relationships. We hypothesize that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In this way, complete matching of the talar prosthesis and the surgical operability of implantation were assured. Joseph Tracey reported no significant changes in the talar width and arc length in 14 patients who underwent the custom 3D-printed total talar prostheses replacement; however, the talar height was significantly increased, and Meary's angle was decreased [17]. In this study, the talar height and Meary's angle were significantly changed, which is similar to the literature.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this way, complete matching of the talar prosthesis and the surgical operability of implantation were assured. Joseph Tracey reported no significant changes in the talar width and arc length in 14 patients who underwent the custom 3D-printed total talar prostheses replacement; however, the talar height was significantly increased, and Meary's angle was decreased [17]. In this study, the talar height and Meary's angle were significantly changed, which is similar to the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Functional exercises of dorsiflexion and flexion were performed to improve the range of ankle motion. The accuracy of the postoperative reconstruction with respect to the preoperative plan was evaluated in terms of the talar arc length, talar height, talar width, tibial alignment angle, talar tilt angle, Bohler's angle, and Meary's angle [17]. As well as strict follow-up from the first day after operation, imaging data were taken regularly and compared with those before operation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study on the implant design used in this paper demonstrated that this custom 3D printed implant restored native talar anatomy with regard to talar height and talar tilt. 19 The improvement in self-reported pain following TTR is not surprising given the significant improvement in function discussed previously. It is important to note that the final mean VAS score in the present study was 4; although a significant improvement was seen, some patients still reported pain.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, some authors published their results using different total talar replacement. 1416 The overall survival rate varies from 85% to 100%. Although this kind of procedures seems to be technically easy to perform, it does not allow too many options in case of revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…13 Also, in order to maintain mobility, some authors published their results using a total talar replacement such as alumina ceramic prosthesis, 14 stainless-steel talar body prosthesis 15 and nickel-plated cobalt implants. 16…”
Section: Introductionmentioning
confidence: 99%